Profil Kerjasama Mahasiswa dalam Kegiatan Praktikum - Ita Ita (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2021)
Students are part of community who will participate in social interactions. Mastery of social skills is expected to be able to equip graduates to interact in more complex societies. One of social skill is cooperation. Therefore, ability to cooperation is important. Student interaction in completing assignments when practicum activities become a means of building cooperation between group members. Practicum subject at Biology Education of FTK UIN Antasari Banjarmasin are presented in the third semester. Student cooperation should have been well developed because so far they have become accustomed to interacting in class. Facts in the field apparently show that the level of student ccooperation is still low. Plant morphology practicum is expected to play a role in increasing the level of cooperation between students. This study aims to describe the profile of cooperation between students in practicum activities. Data collection was carried out through observation and interviews with students. Practicum can facilitate students to build cooperation in their groups. In general, the percentage of cooperation increased from practicum 1 to practicum 9. If viewed on group basis, group cooperation ranges from fairly good to good. The group with the lowest average cooperation was obtained by group 1 and the highest group 6.